Rogério Andrade Barbosa's contributions to Afro-Brazilian literature (Research, Society and Development, 2020)
This article discusses Rogério Andrade Barbosa's contributions to Afro-Brazilian literature, since the same in his short stories highlights the history of the griots and in his books “the son of the wind” and “how the stories spread throughout the world” and are brought into Brazilian literature. The objective is to highlight the representation of griots in African culture and the way in which this representation is configured in narratives of Brazilian literature, problematizing the use of European literature to the detriment of Afro-Brazilian literature in schools. There is a demonstration of the historical process of blacks and their ways of preserving oral tradition. The griots are considered as guardians of history and through the use of orality they transmit their knowledge from generation to generation. Thus, the author uses these tales in order to distance Portuguese literature and valuing Afro-Brazilian literature, as it is relevant for the student to know the history of his ancestors to value and respect.